Isolation and Identification of Gram Negative Bacteria from Chicken Meat collected from Retail Meat Shops of Kathmandu Valley - Koirala, B; Bhattarai, R; Maharjan, R; Maharjan, S; Shrestha, S (Nepalese Veterinary Journal, 2023)
Available within the full text